Exceptionally High Hatchability of Vanaraja Hatching Eggs under Field Conditions- A Success Story - Khan, A. A.; Reshi, Parvez A.; Haq, Zulfqarul; Simnani, S. A. (Indian Journal of Hill Farming, 2019)
One hundred and fifty Vanaraja hatching eggs were provided to 15 tribal farm women for natural incubation using broody hen. The freshly collected hatching eggs were sorted and clean eggs of uniform size, ideal shape, texture were separated. The eggs were pre-candled to remove the eggs with shell deformities, hairline cracks etc. Training with regards to  selection of broody hen, preparation of the egg nests, feeding, care and management of brooding hen during the period of incubation was provided prior to setting of eggs for incubation. The overall hatchability on total eggs set (HTES) was 98% and hatchability onfertile eggs set (HFES) was 98.66%. The farmers were quite satisfied with the results of incubation and having hatched the chicks through natural incubation at their premises, farmers showed more involvement and care in rearing the chicks. The success story demonstrates that excellent hatchability under natural incubation could be achieved through careful selection of hatching eggs, less pre-incubation holding period of the eggs, optimum brooding nest material.